Expanding Vocabulary Through the Use of Multilingual Reading Materials in Preschool Period - Bednjički Rošer, Barbara; Voršič, Ines (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
The chapter focuses on vocabulary development in preschool children exploring multilingual literary and informative reading materials, namely a literary picture book and picture dictionaries. We conducted a case study to examine the familiarity with animals, i.e. the ability to name individual animals in Slovenian, in preschool children of the second age group (5–6 years). A total of 25 children (n = 25) participated in the study: 11 with Slovenian as their native language and 14 who learn Slovenian as a second language. The study results demonstrate significant differences in the naming of selected animals between children born in Slovenia and immigrant children. A particularly disquieting finding is that children who are soon to enter school have difficulty naming animals not only in Slovenian, but also in their mother tongue.